Food and nutrition profile of pregnant adolescent - Pajuelo R., Jaime (2015)
OBJECTIVE.- To determine the nutritional status Of pregnant adolescents. PATIENTS: We studied 177 pregnant adolescents 15 to 19 years of age, attended at Dos de Mayo and Santa Rosa Hospitals. Weight and height were taken to the entire population. Arm perimeter and triceps skinfold thickness were measured to 56 patients. With the first two, the Quetelet index was calculated and with the latter ones the muscular and fat areas. For the IQ analysis the Must et al reference was used; arm ratios were analyzed with Frisancho's reference. In 56 adolescents Hb was dosed (11 gr/dL). Their quantitative consumption of energy and nutrients was appraised to 54. RESULTS: Anemia was found in 62,5% of the pregnant adolescents. No supplementation is received by 77% of them; 10% of the pregnant show low weight during the first trimester. About 6 to 8% show a light decrease in their ratios of fat and magre deposits respectively. CONCLUSIONS: Seventy of the pregnant adolescents receive an adequate intake of energy, proteins, retinol and C vitamin. Iron and calcium intakes are very low.